Cytokine production of mononuclear leukocytes in response to respiratory syncytial virus is increased in COPD but suppressed in non-COPD tobacco smokers - Sarah D. Yanik; Kaschin Jamal Jameel; Simon Rohde; Paul Bürger; Eike Bülthoff; Thomas Grunwald; Juliane Kronsbein; Andrea Koch; Michael R. Edwards; Matthias Tenbusch; Jürgen Knobloch (Molecular Medicine)
Abstract Background Respiratory syncytial virus (RSV) induces exacerbations of chronic obstructive pulmonary disease (COPD) that are critical for disease progression and burden. COPD subjects have an increased susceptibility to viral respiratory infections. We aimed to identify underlying systemic immune pathologies that could be used as drug targets to reduce exacerbations. Methods Peripheral blood mononuclear cells were isolated from 16 healthy never smokers, 17 current smokers without airflow limitation, and 17 COPD subjects. The cells were cultured and infected with RSV for 24 h or seven days. IFNα, T-cell- and inflammatory cytokines, the expression of interferon-stimulating genes (ISGs), and virus load in supernatants were measured by ELISA or real-time PCR, respectively. Data were compared between the three patient groups. Results RSV induced CCL2, CCL5, IFNα, IFNγ, IL1-β, IL-6, IL-8, and TNFα but not IL-4, IL-5, IL-17, GM-CSF, and TGFβ. CCL2 was unchanged between the groups. All other cytokines were either increased or produced for a longer period of time in COPD but were reduced or not produced at all in smokers. Virus copy numbers were increased in COPD but reduced in smokers. RSV induced MxA, OAS, and Viperin expression with differences between the groups. Conclusion Circulating immune cells in COPD might cause cytokine overproduction in response to RSV after recruitment to the site of infection and might contribute to the increase in inflammation in exacerbations. This might be explained by differences in RSV replication efficacy and ISG expression. We provide first indication for ISGs and circulating cells as drug targets to reduce or prevent exacerbations.